P. Dovydaitis’ Natural Philosophical Views - Balčius, Jonas (Problemos, 1981)
In his works, P. Dovydaitis, an ideologist of Lithuanian clerical bourgeoisie, was striving to prove indissolubility of Neo-Thomist philosophy (its world-outlook theses) as well as natural scientific cognition in the field of biology (especially in embryology, genetics, etc.). It was he who came out as an active supporter to theologize Ch. Darwin’s doctrine, propagated vitalistic conceptions of some biologists (including G. Driesch and J. Reinke). A critical analysis of P. Dovydaitis’ principal theses and arguments, antiscientific character and conceptual inconsistency of his views are presented in the article.